Visualization in participatory program (VIPP) - Rakib-Ul-Hoque; Alam, Shariful (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2006.